Squeezing Film Characteristics for Micropolar Fluid between Porous Parallel Stepped Plates - A. Siddangouda (Tribology in Industry, 2015)
In this paper, the theoretical study of squeeze film characteristics between porous parallel stepped plates with non-Newtonian micropolar fluid is presented. The lubricant in the film region and also in the porous is modeled as Eringen’s micropolar fluid. A non-Newtonian modified Reynolds equation is derived for porous parallel stepped plates and applied to obtain solution of squeeze film characteristics. Comparing with the classical Newtonian lubricant case, the influence non-Newtonian micropolar fluids are found to enhance the load carrying capacity and lengthen the approaching the time of porous parallel stepped plates. The load capacity decreases as the step height increases.